Increased 18F-FDG accumulation in less-affected lung area in patients with non-small cell lung cancer and postoperative acute exacerbation of interstitial lung disease. Issue 135 (February 2021) - Fukunaga, Kentaro; Nagatani, Yukihiro; Nakagawa, Hiroaki; Nitta-Seko, Ayumi; Nagata, Tamotsu; Nishizono, Masaki; Kobashi, Kazumasa; Iguchi, Harumi; Nitta, Norihisa; Hanaoka, Jun; Murata, Kiyoshi; Watanabe, Yoshiyuki; et al.
Highlights: 18 F-FDG accumulation in normal-appearing lung may reflect regional invisible fibrosis and inflammatory change. 18 F-FDG PET/CT may predict postoperative exacerbation in NSCLC patients. SUVmean in normal-appearing lung should be noted in NSCLC patient with ILD. Abstract: Purpose: To investigate whether or not 18 F-FDG accumulation in normal or less-affected lung fields increased in non-small cell lung cancer (NSCLC) patients with postoperative acute exacerbation (PAE) of interstitial lung disease (ILD) Material and methods: Thirty-six NSCLC patients with ILD and 50 patients without ILD (non-ILD patients) underwent pre-operative 18 F-FDG-PET/CT at 2 institutions. Volume-of-interest (VOI) was placed to measure the mean standardized uptake value (SUVmean ) in normal or less-affected lung fields at pre-defined 12 areas on ventral and dorsal locations of both lungs. SUVtissue fraction (TF) was defined as corrected SUVmean by using TF and mean computed tomography density on PET/CT. Harmonized SUVmean (hSUVmean ) and SUVTF (hSUVTF ) were calculated based on results of phantom study, which was performed to optimize the measured SUV difference among 2 institutions. Both the h-SUVmean and the h-SUVTF were compared between 8 patients with PAE of ILD (PAE group) or remaining 28 patients without PAE of ILD (non-PAE group) and non-ILD patients in each of the 12 areas. Results: The hSUVmean in PAE group was higher in 9 out of 12 locations as compared with non-ILD patients, whereas the hSUVmean was mostly similar between non-PAE group and non-ILD patients. In contrast, the hSUVTF in non-PAE group was similar to that in PAE group, and higher than in non-ILD patients in most locations. Conclusion: 18 F-FDG-PET/CT demonstrated increased SUVmean along with elevated SUVTF in normal or less-affected lung fields for NSCLC patients with PAE of ILD, which may reflect regional invisible fibrosis and inflammatory change.